Measurement of CP violation and constraints on the CKM angle γ in B±→DK± with D→KS0π+π− decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Nuclear physics. B, Particle physics, 2014)
A model-dependent amplitude analysis of B±→DK± with D→KS0π+π− decays is performed using proton-proton collision data, corresponding to an integrated luminosity of 1 fb−1, recorded by LHCb at a centre-of-mass energy of 7 TeV in 2011. Values of the CP violation observables x± and y±, which are sensitive to the CKM angle γ, are measured to bex−=+0.027±0.044−0.008+0.010±0.001,y−=+0.013±0.048−0.007+0.009±0.003,x+=−0.084±0.045±0.009±0.005,y+=−0.032±0.048−0.009+0.010±0.008, where the first uncertainty is statistical, the second systematic and the third arises from the uncertainty of the D→KS0π+π− amplitude model. The value of γ is determined to be (84−42+49)°, including all sources of uncertainty. Neutral D meson mixing is found to have negligible effect.
Im Titel sind die Zeichen "+/-", "+", "-" sowie die Zahl "0" hochgestellt, der Buchstabe "S" ist tiefgestellt, dabei steht "0" über "S"
*LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und 669 weitere Personen]